2015
DOI: 10.1097/ncc.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Caregiving and Sleep Disturbance Among Family Caregivers of Advanced Cancer Patients

Abstract: Family caregivers with risk factors for sleep disturbance should be identified and be provided resources for sleep quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 45 publications
3
67
2
1
Order By: Relevance
“…These findings strongly support further research of the dyadic effects of distress on sleep to identify longitudinal effects on holistic sleep outcomes for those coping with advanced cancer and their caregivers. Despite numerous interventions targeting sleep disturbance in cancer patients, a significant portion of advanced cancer patients and caregivers still report poor sleep . To maximize effectiveness, interventions for sleep disturbance in cancer patients or caregivers may benefit from including strategies for coping with a partner's anxiety or including both members of the couple.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These findings strongly support further research of the dyadic effects of distress on sleep to identify longitudinal effects on holistic sleep outcomes for those coping with advanced cancer and their caregivers. Despite numerous interventions targeting sleep disturbance in cancer patients, a significant portion of advanced cancer patients and caregivers still report poor sleep . To maximize effectiveness, interventions for sleep disturbance in cancer patients or caregivers may benefit from including strategies for coping with a partner's anxiety or including both members of the couple.…”
Section: Discussionsupporting
confidence: 52%
“…Short sleep duration is one of the most commonly reported forms of sleep disturbance among cancer caregivers, 10 and previous work has demonstrated that both cancer patients and caregivers report getting less than the recommended minimum amount of sleep per night. 3,6,11,12 Subjective sleep duration is directly associated with meaningful clinical outcomes, including many physical health conditions, 3,13,14 all-cause and cancer-specific mortality, 14,15 as well as survival in advanced cancer patients. 3 Importantly, sleep duration is also associated with various mental health conditions, including anxiety and depression.…”
Section: Sleep Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the sample was relatively small in size to investigate the potential effects of sex, age, or treatment status. Fifth, other relevant confounding factors, such as treatment status, pain and other physical symptoms, financial situation, and caregiver burden, were not investigated . Last, the directions of effects cannot be informed in this cross‐sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…for his/her family and relatives, and due to the responsibility that it places on the caregiver, it can be perceived as a burden of care. [3][4][5] The burden of care is one of the most serious problems for family caregivers who look after a family member with a chronic progressive disease. The burden of care causes the caregiver to delay his/her needs and leads to negative experiences such as reduced interpersonal relationships and impaired physical health, which later affect the caregiver's wellbeing level and can cause him/ her to experience emotional changes such as stress.…”
mentioning
confidence: 99%